TAMU DAN PERSIDEN KARYA WISRAN HADI : KAJIAN HISTORIOGRAFI TENTANG MASA ORDE BARU DAN AWAL REFORMASI DI MINANGKABAU - Mutia Fadila; Hendra Naldi (Jurusan Sejarah FIS UNP, 2021)
This research examines the New Order period and the beginning of the Reformation in Minangkabau through two literary novels entitled Tamu and Persiden by the writer Wisran Hadi. Previously, there had been a lot of research on the New Order and the beginning of the Reformation in Indonesia, but it is still rare to find research that specifically sets the discussion on an ethnicity, such as the Minangkabau ethnicity. The two novels are able to provide an overview of how the two periods took shape in Minangkabau, through the author’s criticism mixed with the cultural elements of the local community. This study aims to provide an overview of the New Order period and the Beginning of the Reformation in Minangkabau. The method used in this research is the library method by going through four stages, starting from preparing research support tools, collecting works (bibliography), time management, to making notes of the results. There are several findings in this study including: (1) The description of the New Order and the beginning of the Reformation in Minangkabau related to political deviations, controversial development efforts, and changes in the traditional value order of Minangkabau society. (2) Wisran Hadi's background as a writer from the 70's and his life history which cannot be separated from Minangkabau, influenced the depiction of the New Order period and the beginning of the Reformation in Minangkabau. (3) The depiction of the two periods in the novels Tamu and Persiden shows their relevance to contemporary works. Keywords: Historiografi, Karya Sastra, Orde Baru dan Reformasi, Minangkabau